2020
DOI: 10.1155/2020/9610261
|View full text |Cite
|
Sign up to set email alerts
|

Are Stem Cells Derived from Synovium and Fat Pad Able to Treat Induced Knee Osteoarthritis in Rats?

Abstract: Background. Osteoarthritis (OA) is a chronic disease and a significant cause of joint pain, tenderness, and limitation of motion. At present, no specific treatment is available, and mesenchymal stem cells (MSCs) have shown promising potentials in this regard. Herein, we aimed to evaluate the repairing potentials of stem cells derived from the synovium and fat pad in the treatment of OA. Methods. Twenty-eight male rats (220±20 g, aged 10-12 weeks), were randomly divided into four groups (n=7): C1: nontreated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Four mg collagenase II (clostridium histolithicum; Sigma-Aldrich, St. Louis, MO, USA) dissolved in sterile PBS, and afterward was injected in the knee intra-articular space. After 3 days, injection was repeated [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four mg collagenase II (clostridium histolithicum; Sigma-Aldrich, St. Louis, MO, USA) dissolved in sterile PBS, and afterward was injected in the knee intra-articular space. After 3 days, injection was repeated [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three months after onset of treatment, rats were killed in a CO 2 chamber, and thereupon radiography was taken from the lateral aspect of knee joint using radiographic equipment (AxiomMultix M Radiographic Unit, SiemensTM, Germany). Osteoarthritis in terms of presence of osteophytes, joint space narrowing, and subchondral sclerosis as Radiological grading system was assessed by a blinded radiologist [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Synovium-derived mesenchymal stem cells (S-MSCs) have attracted considerable attention due to their high chondrogenic potential, and are recognized as a viable option to repair cartilage [ 124 , 125 ]. Zare et al conducted a research study on rats wherein animals treated with S-MSCs showed significantly better results in every pathological evaluated criterion compared to control, HA and ADSCs groups [ 126 ]. Furthermore, another research study reported the efficacy of S-MSCs in OA treatment, showing a significant reduction in serum inflammatory factors and cartilage protection thanks to the upregulation of chondrogenic gene expression in meniscus chondrocytes [ 127 ].…”
Section: Bioregenerative Therapies In Osteoarthritismentioning
confidence: 99%
“…During the past decades, the existence of highly regenerative mesenchymal stem cells was et al 2020; Zare et al 2020) . Furthermore, the MSC numbers obtained from adipose tissue are much higher than from the bone marrow (Wolfstadt et al 2015).…”
Section: Articular Cartilage Degradationmentioning
confidence: 99%
“…Especially ASCs are of great interest, which have been shown to prevent OA development in rats (Zare et al 2020) and to reduce pain and regenerate cartilage in OA patients after intraarticular injection (Freitag et al 2020). In order to repair the damaged cartilage, the highly proliferative sASCs with greater chondrogenic capacity in producing ECM molecules would be advantageous compared with the limited proliferative and chondrogenic function of mature chondrocytes (McGonagle, Baboolal, and Jones 2017).…”
Section: Ne Influences the Regenerative Potential Of Sascsmentioning
confidence: 99%